2018
DOI: 10.1007/s40273-018-0740-4
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab in Combination with Chemotherapy for the First-Line Treatment of Patients with Advanced Follicular Lymphoma

Abstract: The National Institute for Health and Care Excellence (NICE), as part of the institute’s single technology appraisal (STA) process, invited the company that makes obinutuzumab (Roche Products Limited) to submit evidence of the clinical and cost effectiveness of the drug in combination with chemotherapy, with or without obinutuzumab as maintenance therapy for adult patients with untreated, advanced follicular lymphoma (FL) in the UK. Kleijnen Systematic Reviews Ltd (KSR), in collaboration with Erasmus Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The cost-effectiveness of G was evaluated in Western countries. The National Institute for Health and Care Excellence (NICE) recommended the use of G for both untreated and advanced FL patients under the patient access scheme [9][10][11] . G was also assessed in a US setting and found that treatment with G þ Chemo against R þ Chemo was more cost-effective in patients with previously untreated FL 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effectiveness of G was evaluated in Western countries. The National Institute for Health and Care Excellence (NICE) recommended the use of G for both untreated and advanced FL patients under the patient access scheme [9][10][11] . G was also assessed in a US setting and found that treatment with G þ Chemo against R þ Chemo was more cost-effective in patients with previously untreated FL 12 .…”
Section: Introductionmentioning
confidence: 99%